Розробка мобільного додатку для підбору одягу - Надточій, О. Ю. (ХНУРЕ, 2019)
In order to facilitate a selection of men's clothes by potential customer the mobile application was developed. The main advantages of this application are an option to get information about clothes as well as 3D model of manneken which enables an adjustment of individual geometric parameters of user.